Study on Dissolution and Regeneration of Poplar Wood in Imidazolium-Based Ionic Liquids - Vo, Huyen Thanh; Kim, Chang Soo; Ahn, Byoung Sung; Kim, Hoon Sik; Lee, Hyunjoo (TAYLOR & FRANCIS INC, 2011)
We tested dissolution and regeneration of poplar wood using 1-butyl-3-methylimidazolium chloride ([C(4)mim]Cl) and 1-butyl-3-methylimidazolium acetate ([C(4)mim]OAc). When 5wt% of poplar sawdust in [C(4)mim]OAc was stirred at 130 degrees C, 96wt% of added poplar was dissolved in [C(4)mim]OAc, whereas 25.3wt% of poplar dissolved in [C(4)mim]Cl at the same reaction condition. Fourier transform infrared spectroscopy (FT-IR) and lignin content analysis revealed that poplar was partially delignified during the dissolution and regeneration processes. X-ray diffraction (XRD), thermal gravimetric analysis (TGA), and microscopy were used to characterize raw poplar sawdust, undissolved poplar, and regenerated wood from the poplar-ionic liquid solution. The direct acetylation of poplar-[C(4)mim]OAc solution using acetyl chloride was also performed in the absence of any organic solvent. FT-IR analysis of the resulting wood sample revealed the formation of partially delignified acetylated-poplar.
Keywords: CELLULOSE DISSOLUTION; LIGNOCELLULOSIC MATERIALS; SOLID BIOMASS; SOLVENT; MECHANISM; CHLORIDE; LIGNIN